Compensations of top executives and M&A behaviors: An empirical study of listed companies - Jiao Xue; Heng Fan; Zhanxun Dong (International Journal of Financial Studies, 2020)
This study empirically examines the relationship between executive compensation and mergers and acquisitions (M&A) behaviors by identifying the influence of short- and long-term incentive on the propensity and scale of M&A. When the short-term incentive is insufficient, M&A behaviors serve as a beneficial compensation mechanism. Thus, lack of executives' incentive promotes the propensity to engage in M&A and significantly affects the scale of M&A.With regard to long-term incentives, M&A behaviors serve as a beneficial creation mechanism. Shareholding of executives promotes M&A propensity, and does not significantly affect the scale of M&A. This study significantly contributes to research in M&A behaviors by revealing the beneficial distribution mechanisms of M&A behaviors.
Keywords: G34; M52; N25; 330; mergers and acquisitions behaviors; executive compensation incentive; beneficial distribution mechanisms; listed companies